SOCIAL REPRESENTATIONS OF PRIMARY HEALTH CARE NURSES ABOUT NURSING CARE IN THE POSTPARTUM PERIOD - Sibele Lima da Costa Dantas; Dafne Paiva Rodrigues; Ana Virgínia de Melo Fialho; Eryjosy Marculino Guerreiro Barbosa; Ana Maria Martins Pereira; Nayara Sousa de Mesquita (Universidade Federal do Paraná, 2018)
Objective: to gain insight on the social representations of primary health care nurses about nursing care in the postpartum period. Method: Qualitative study based on the Theory of Social Representations, conducted from September to October 2015, with 31 nurses of the Family Health Strategy of the city of Mossoró, Rio Grande do Norte, Brazil, through semi-structured interviews. Data were analyzed with the aid of ALCESTE software, which conducts lexical analysis of text data. Results: It was found that the care provided by nurses prioritizes childcare appointments (care to the newborn) to the detriment of postpartum appointments. Conclusion: Nurses should develop integral postpartum care, which goes beyond the implementation of technical procedures, involving qualified listening and care to the biopsychosocial needs of postpartum women.